Association Between Discoid Lupus Erythematosus and Chronic Granulomatous Disease—Report of Two Cases and Review of the Literature. Issue 2 (March 2016) - Xie, Charles; Cole, Theresa; McLean, Catriona; Su, John C.
Abstract: Discoid lupus erythematosus (DLE) is known to be associated with chronic granulomatous disease (CGD), but most DLE occurs in female carriers of X‐linked CGD, with few reports of these lesions in CGD‐affected individuals—this observation is unexplained. We describe two cases of DLE‐like lesions in boys with CGD: one boy with partial neutrophil function and another whose lesions were related to voriconazole use. Reviewing other previously reported cases, we conclude that the risk of developing DLE‐like lesions appears to be greater primarily in two subsets of the population with CGD: those with partial neutrophil function and those with near‐absent neutrophil function in whom there is a second trigger. In light of recent literature on the role of neutrophils in lupus pathogenesis, we propose that pathogenesis of DLE in CGD may be related to NETosis, neutrophil dysfunction and a deficiency of reactive oxygen species, which medications such as voriconazole also influence.